Fungal Keratitis. Part 1. Etiomorphology, Historical Aspects, Epidemiology, Risk Factors, Pathogenesis and Clinical Features - O. V. Shilovskikh; V. O. Ponomarev; V. L. Timofeev (Oftalʹmologiâ)
Fungal keratitis (FK) is 8–30 % in the structure of infectious inflammation of the cornea. There are 2 main types of mushroom growth — mycelial and yeast. Mycelial (mold) fungi grow in the form of special branched microscopic tubes — hyphae. Yeast fungi form compact colonies of individual oval cells. Due to the peculiarities of the yeast structure, the tendency to rapid spread in the tissues is reduced, which determines the less aggressive clinical course of such keratomycosis compared to mold. Until the 50s of the 20th century, the occurrence of FK in the world was low. However, probably with the introduction of corticosteroid and antibacterial drugs into medicine, their prevalence began to grow. The highest frequency of occurrence of FK is in regions with a hot climate and high involvement of the population in agriculture. The main provoking factor for the appearance of FK is corneal injury with damage to the epithelium and adhesion to the Bowman’s membrane or stroma components. Highly adhesive fungi (Aspergillus spp., Candida spp.) trigger a cascade of immune inflammatory reactions, production of reactive oxygen species and matrix metalloproteases-9, which leads to the destruction of lamellae. Fungi with low adhesive ability (Fusarium spp.) can grow parallel to lamellae for a long time and indefinitely without inducing pronounced inflammation. Symptoms of FC are similar to those observed in other forms of infectious keratitis, but more often they develop more slowly (5–10 days) and are less acute. A defect against the background of mycelial FC is more often characterized by jagged edges, a raised slough, and a non-yellow color. Yeast FK is manifested by oval ulceration of the epithelium with expanding, more sharply demarcated, densely focal suppuration.